1993
DOI: 10.1002/jso.2930530113
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of a cholecystokinin antagonist, loxiglumide (CR‐1505), on the growth of freshly separated and xenografted human pancreatic cancer

Abstract: The effects of cholecystokinin (CCK) and a CCK antagonist, loxiglumide (CR-1505), on four freshly separated and six xenografted human pancreatic cancers, were investigated. The level of DNA synthesis in only one of five tested pancreatic cancers was enhanced by CCK at concentrations of 0.01-10 nM, while in the other four cancers DNA synthesis was not affected. The levels of DNA, RNA, and protein synthesis (by 3H-thymidine, 3H-uridine, and 3H-leucine incorporation tests, respectively) in all the tested cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…These findings are in agreement with other reports: Watanapa et al [19] showed that lorglumide inhibited azaserine pancreatic carcinogenesis after pancreatobiliary diversion in rats; Morimoto et al [20] reported that loxiglumide (CR-1505), another specific CCK receptor antagonist, significantly inhibited the in vivo and in vitro growth of human pancreatic cancer, suggesting that its antitumor activity may be independent of the actual stimulation with CCK or anyway another agonist, and Shivaram et al [21] studied another CCK receptor antagonist, L-364,718, (a nonpeptide compound) that exhibited only a limited activity on the growth of transplantable pancreatic carcinoma in the Syrian hamster.…”
Section: Well-differentiated Duct Adenocarcinorna That Arose In a Fibsupporting
confidence: 91%
“…These findings are in agreement with other reports: Watanapa et al [19] showed that lorglumide inhibited azaserine pancreatic carcinogenesis after pancreatobiliary diversion in rats; Morimoto et al [20] reported that loxiglumide (CR-1505), another specific CCK receptor antagonist, significantly inhibited the in vivo and in vitro growth of human pancreatic cancer, suggesting that its antitumor activity may be independent of the actual stimulation with CCK or anyway another agonist, and Shivaram et al [21] studied another CCK receptor antagonist, L-364,718, (a nonpeptide compound) that exhibited only a limited activity on the growth of transplantable pancreatic carcinoma in the Syrian hamster.…”
Section: Well-differentiated Duct Adenocarcinorna That Arose In a Fibsupporting
confidence: 91%
“…In vivo and in vitro studies have revealed that the CCK/CCK receptor engagement is involved in the proliferation and survival of several tumor cells ( Morimoto et al., 1993 ; Ponnusamy et al., 2016 ; Smith et al., 2016 ). Thus, it is hypothesized that the growth of melanoma and SCC is also regulated by CCKAR signaling.…”
Section: Resultsmentioning
confidence: 99%
“…CCK receptors are expressed not only in normal tissues, but also in various types of cancer, such as pancreatic, colon, and lung cancers (Dufresne et al, 2006, Smith et al, 2016. CCK promotes the proliferation and survival of tumor cells, and thus the blockade of the CCK receptor with its antagonists suppresses the proliferation and induces the apoptosis of tumor cells, leading to the inhibition of tumor growth in vivo (Morimoto et al, 1993, Ponnusamy et al, 2016, Smith et al, 2016. Mathieu et al (2005) reported that selective CCKB receptor antagonists delayed the growth of C32 human melanoma xenografts, which may be attributed to their inhibitory effect on neoangiogenesis (Mathieu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Death was caused by respiratory failure due to severe congestion of the lung after the administration of a large dose of loxiglumide. The growth of a PC-HN transplanted in the nude mice was significantly inhibited by subcutaneous loxiglumide at 250 mg/kg, twice a day for 28 days, which did not cause death [29].…”
Section: Loxiglumide and Proglumide As Early Anti-cancer Agentsmentioning
confidence: 94%